DPR-GR dalam Transisi Kekuasaan Soekarno ke Orde Baru Tahun 1965-1971 - Fathu Shodiqur Rohman (Universitas Veteran Bangun Nusantara, 2025)
This study examines the role and political dynamics of the People's Representative Council of Mutual Assistance (DPR-GR) during the transition of power from the Old Order to the New Order in Indonesia. The main focus is to analyze how DPR-GR, as a legislative body engineered by the Old Order regime, underwent a transformation in function and position amidst the shifting power structure following the 30 September Movement (G30S/PKI). Using a historical-political approach and primary document analysis, this research reveals how DPR-GR was utilized as a tool to legitimize Soeharto’s rise to power and to erode President Soekarno’s authority. The findings show that DPR-GR was not merely a passive observer, but an active agent in the consolidation of military power and the establishment of the New Order regime. This study underscores that the political transition during this period was not solely militaristic, but also involved strategic manipulation of formal political institutions to legitimize the new regime. Keywords: DPR-GR, Transition of Power, Soeharto, New Order